2022
DOI: 10.3390/v14081613
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treatment-Induced Viral Eradication on Cytokine and Growth Factor Expression in Chronic Hepatitis C

Abstract: In this study, we evaluated the effect of hepatitis C virus eradication using direct-acting antivirals (DAA) on the serum cytokine and growth factor profiles of chronic hepatitis C patients (CHC). Serum concentrations of 12 cytokines and 13 growth factors were measured in 56 patients with CHC before, during the DAA treatment and after sustained virological response using bead-based flow cytometry. Cytokine and growth factor levels were also measured in 15 healthy individuals. The majority of the selected cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, our data are consistent with recent studies focusing on non-cirrhotic chronic HCV patients that demonstrated decreased ISG expression after viral elimination 30 . On the other hand, other previous studies suggested that cytokine alterations may still persist in all chronic HCV patients 31 . However, in addition to fibrosis and cirrhosis, other factors may also influence the regeneration of the inflammatory milieu after HCV elimination.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, our data are consistent with recent studies focusing on non-cirrhotic chronic HCV patients that demonstrated decreased ISG expression after viral elimination 30 . On the other hand, other previous studies suggested that cytokine alterations may still persist in all chronic HCV patients 31 . However, in addition to fibrosis and cirrhosis, other factors may also influence the regeneration of the inflammatory milieu after HCV elimination.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, gene expression levels were measured in peripheral blood samples, implying that extrapolation of our results to liver tissue should be done with caution. However, different studies suggest that the immunomodulatory effects of CHC infection are detectable on the systemic level, especially in the case of CHC patients without other underlying conditions [24,33,34]. Finally, there was a significant difference in sex distribution between the patient and healthy control groups, with all healthy controls being female.…”
Section: Discussionmentioning
confidence: 92%
“…Chronic HCV infection is associated with systemic immune activation and elevated levels of interferons, inflammatory biomarkers including IL-6 and TNF/TNF receptors, chemokines such as CXCL10 and markers of myeloid cell activation including soluble (s) markers sCD163 and sCD14 ( 8 13 ). Conflicting data exist regarding the impact of HCV elimination on reversal of immune activation; whilst some biomarkers including CXCL10, IL-10 and sCD163 are consistently reduced following HCV elimination ( 8 , 9 , 13 18 ), others including IL-6, TNF and sCD14 are unaffected or inconsistently altered by DAA therapy ( 9 , 13 16 ). Importantly, numerous studies suggest that DAA therapy does not restore levels of many parameters including sCD163 and CXCL10 to those found in comparable, HCV-seronegative populations ( 8 , 13 , 14 , 17 19 ).…”
Section: Introductionmentioning
confidence: 99%